Acute Symptomatic Seizures and Risk of Epilepsy in Autoimmune Encephalitis: A Retrospective Cohort Study - Zhong, Rui; Zhang, Xinyue; Chen, Qingling; Li, Mengmeng; Guo, Xin; Lin, Weihong (Frontiers in Immunology, 2022)
Abstract Purpose: To investigate the clinical characteristics of acute symptomatic seizures and the predictors of the development of epilepsy in patients with anti-NMDAR, anti-LGI1, and anti-GABABR encephalitis. Methods: We retrospectively screened the medical records of 86 hospitalized patients with confirmed autoimmune encephalitis (AE). The clinical characteristics of acute symptomatic seizures were analyzed. The predictors of the development of epilepsy were investigated using logistic regression analysis. Results: A total of 86 patients with AE were finally included. Eighty-six percent of patients (n = 74) experienced acute symptomatic seizures, and 28.4% of patients developed epilepsy during follow-up. Abnormal EEG findings were more frequent in AE patients with acute symptomatic seizures. A greater number of anti-seizure medications (ASMs), abnormal EEG findings, and delayed immunotherapy were found to be independently associated with the development of epilepsy. Conclusion: Acute symptomatic seizures are a common manifestation in AE patients. During follow-up, 28.4% of AE patients developed epilepsy. The independent factors that predicted the development of epilepsy after the acute phase included a larger number of ASMs, EEG abnormalities, and delayed immunotherapy. In clinical practice, we should prioritize immunotherapy to control acute seizures as soon as possible. For AE patients with an increased risk of developing epilepsy, early withdrawal of ASM is not recommended.